Cost and cost-effectiveness of three strategies for implementing motivational interviewing for substance misuse on medical inpatient units. (1st September 2020) - Olmstead, Todd A.; Yonkers, Kimberly A.; Forray, Ariadna; Zimbrean, Paula; Gilstad-Hayden, Kathryn; Martino, Steve
Highlights: Economic analysis of implementing MI for substance misuse on medical inpatient units. Workshop, apprenticeship, and consult implementation strategies were examined. All three strategies were economically unattractive from hospital perspective. Workshop and apprenticeship had high start-up costs and low uptake. Consult's ongoing costs were not covered by existing reimbursements. Abstract: Background: This study conducted cost and cost-effectiveness analyses of three strategies for implementing motivational interviewing for substance misuse on general medical inpatient units: workshop, apprenticeship, and consult. Methods: The economic analyses were conducted prospectively alongside a type 3 hybrid effectiveness-implementation randomized trial comprising 38 medical providers, 1173 inpatients, and four consultation-liaison motivational interviewing experts. The trial took place in a university affiliated teaching hospital in New Haven, CT, USA. After completing a 1-day workshop on motivational interviewing, providers were randomized to conditions. The primary outcome measure was the number of study-eligible patients who received a motivational interview. The economic analyses included the costs of both start-up and on-going activities in each condition. Incremental cost-effectiveness ratios were used to determine cost effectiveness. Results are presented from the healthcare provider (i.e., hospital) perspective in 2018 US dollars. Results: The total cost per patient receiving a motivational interview averaged 804.53, 606.52, and 185.65 for workshop, apprenticeship, and consult, respectively. Workshop and apprenticeship were extended dominated by the combination of consult and doing nothing. Doing nothing is cost effective when the willingness-to-pay for an additional patient receiving a motivational interview is less than 185.65, and consult is cost-effective when the willingness-to-pay for an additional patient receiving a motivational interview is greater than 185.65. Conclusions: Given that typical reimbursements for brief intervention services for substance misuse are 35-65, none of the three implementation strategies is likely to be economically viable from the healthcare provider perspective.